The world that perished - Whitcomb, John C, Jr. (Grand Rapids, MI Baker, 1973)
Includes bibliographical references indexes, and photographs.
Keywords: Bible. O.T. Genesis -- criticism, interpretation, etc; Deluge -- evidence